Foto polos abdomen megaureter kongenital pada kecurigaan cystoma ovari maligna: Laporan kasus - Rein Matondang; Ni Nyoman Margiani (DiscoverSys Inc., 2020)
Background: Megaureter defined as dilated ureter with or without dilatation of the renal pelvis and calyces.Â Megaureter is a common diagnosis in children, representing 23% of children with urinary tract obstruction. The diagnosis is more common in boys than girls, and more often is on the left side.Case description: A 17-year-old female was referred with a suspicion of malignant ovarian cystoma. On examination, the abdomen was distended.Â Plain radiograph of the abdomen revealed ground glass appearance in abdominal-pelvic cavity suspected of abdominal mass. An ultrasound of the abdomen revealed moderate right hydronephrosis and severe left hydronephrosis. Abdominal CT Scan with contrast demonstrated grade II right hydronephrosis with proximal hydroureter and grade III-IV left hydronephrosis, no solid mass in abdomen. Gynecologyst suspected this patient with left ovarian cystic mass. During the operation, evaluation to obtained ovarian cystic mass was done, yet no mass was obtained. They found a left mega ureter from proximal to distal suspected of a congenital giant mega ureter, followed by left nefrectomy and ureterectomy.Conclusion: A ground glass appearance in plain x-ray may mimicking as hydronephrosis or gynecological mass, particularly in young female patients with suspicion of abdominal mass.Â Latar belakang: Megaureter didefinisikan sebagai ureter yang melebar dengan atau tanpa dilatasi pelvis renalis dan calix ginjal. Megaureter adalah diagnosis yang umum pada anak-anak, mewakili 23% diagnosis pada anak-anak dengan obstruksi saluran kemih. Diagnosis ini lebih sering terjadi pada anak laki-laki daripada anak perempuan, dan lebih sering di sisi kiri.Deskripsi kasus: Seorang wanita berusia 17 tahun dirujuk dengan kecurigaan sistoma ovarium maligna. Pada pemeriksaan, perut tampak distensi. Foto polos abdomen menunjukkan ground glass appearence di rongga perut-panggul yang diduga massa abdomen. Ultrasonografi abdomen menunjukkan hidronefrosis kanan sedang dan hidronefrosis kiri berat. CT-Scan abdomen dengan kontras menunjukkan hidronefrosis kanan derajat II dengan hidroureter proksimal dan hidronefrosis kiri derajat III-IV, tidak tampak massa padat di perut. Dicurigai suatu massa kistik ovarium kiri. Selama operasi, dilakukan evaluasi untuk menemukan massa kistik ovarium, namun tidak didapatkan. Ditemukan megaureter kiri dari proksimal ke distal yang diduga sebagai giant megaureter kongenital, dilanjutkan nefrektomi kiri dan ureterektomi.Kesimpulan: Suatu gambaran ground glass appearance pada foto polos dapat menyerupai hidronefrosis atau masa ginekologi terutama pada wanita muda yang dicurigai massa abdomen.